The Potential Role of Human Papillomavirus Infection in Bell's Palsy: A Hypothesis-Generating Study Based on a Nationwide Cohort - Li, Kuan-Ying; Chou, Mei-Chia; Chang, Renin; Yip, Hei-Tung; Hung, Yao-Min; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Objective: Our purpose was to investigate whether people with a previous human papillomavirus (HPV) infection were associated with an increased risk of Bell's palsy (BP). Methods: By using Taiwan population-based data, patients aged > 18 years with HPV infection (n = 22,260) from 2000 to 2012 were enrolled and compared with control subjects who had never been diagnosed with an HPV infection at a 1:4 ratio matched by sex, age, index date, and co-morbidities (n = 89,040). The index date was the first date of HPV diagnosis. All the patients were tracked until the occurrence of BP. Cox proportional hazards regression was applied to estimate the hazard ratios (HRs) for the development of BP in both groups. Results: The HPV group had 1.25 [95% confidence interval (CI) = 1.03–1.51] times higher risk of BP compared with the non-HPV group after adjusting for sex, age, and co-morbidities. The association of HPV and BP was significant in the sensitivity analyses. In the subgroup analysis, the impact of HPV infection on the risk of BP was more pronounced in the elderly > 50 years [adjusted hazard ratio (aHR) =1.86; 95% CI = 1.37–2.52], hypertension (aHR = 1.65; 95% CI = 1.17–2.31), and chronic obstructive pulmonary disease (aHR = 2.14, 95% CI 1.333.43) subgroups. Conclusions: Patients with HPV infection have a higher risk of subsequent BP compared with non-HPV patients. More rigorous studies are needed to confirm if and how specific HPV genotypes are associated with BP and the possible role of vaccines in disease prevention.